Poemhood, our black revival : history, folklore & the Black experience: a young adult poetry anthology - McBride, Amber; Byas, Taylor (Poet); Martin, Erica (Halcyenda Erica); Alexander, Kwame; Alleyne, Lauren K.; Asim, Jabari, 1962-; Baldwin, James, 1924-1987; Brooks, Gwendolyn, 1917-2000; Browne, Mahogany L.; Carson, DeeSoul; Clifton, Lucille, 1936-2010; Comrie, Courtne; et al. (HarperTeen, an imprint of HarperCollinsPublishers, 2024)
Featuring contributions from an award-winning, bestselling group of Black voices, past and present, this powerful poetry anthology elicits vital conversations about race, belonging, history and faith to highlight Black joy and pain.